High Verdet constant Ga : S : La : O chalcogenide glasses for magneto-optical devices - Pedroso, C. B.; Munin, E.; Villaverde, A. B.; Neto, JAM; Aranha, N.; Barbosa, L. C. (Spie-int Society Optical Engineering, 1999)
The magneto-optical rotation at room temperature was measured for three Ga:S:La:O chalcogenide glasses at several laser lines in the visible. The first sample was a binary system constituted by 70 mol % Ga2S3 and 30 mol % La2O3, whereas in the second and third ones the lanthanum oxide was partially substituted by lanthanum sulfide, keeping the amount of gallium sulfide fixed. A pulsed magnetic field between 50 and 80 kG was used for the Faraday rotation measurements. The Verdet constant for one of the ternary samples was found to be as high as 0.205 min G(-1) cm(-1) at 543 nm, indicating that these chalcogenide glasses are very promising for magneto-optical applications. The data for each sample were fitted using the expected analytical expression for the magneto-optical dispersion. Measurements of the refractive index of the glasses at 632.8 nm are also reported. Data on the magneto-optical properties of two high Verdet constant, heavy-metal oxide diamagnetic glasses are also included for comparison. (C) 1999 Society of Photo-Optical Instrumentation Engineers. [S0091-3286(99)00102-6].
Keywords: magneto-optical Faraday effect; chalcogenide glasses